A Characterization of Interim Efficiency with Public Goods - Ledyard, John O.; Palfrey, Thomas R. (Econometrica, 1999)
In this paper, we consider the following classical public goods problem. A group of individuals must decide on a level of public good that is produced according to constant returns to scale up to some capacity constraint. In addition to deciding the level of public good, the group must decide how to tax the individuals in the group in order to cover the cost. The distribution of the burden of taxation is important because different individuals have different marginal rates of substitution between the private good (taxes) and the public good, and may have different incomes as well. These individual marginal rates of substitution are private information; that is, each individual knows his or her own marginal rate of substitution, but not those of the other members of the group. Adopting a Bayesian mechanism design framework, we assume that the distribution of marginal rates of substitution is common knowledge.